2009
DOI: 10.1167/9.10.5
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between object spatial profile and accommodation microfluctuations in emmetropes and myopes

Abstract: The accommodation microfluctuations are thought to be used by the accommodation controller to obtain information about the direction and magnitude of the required response by monitoring changes in the contrast gradient of this image. The contrast gradient can be altered by presenting different spatial frequency (SF) targets to the eye. Twelve myopes (MYOs) and 12 emmetropes (EMMs) viewed sine and square wave targets of SF 0.5, 1, 2, 4, 8, 16 cpd in a Badal optical system. Accommodation responses were recorded … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
35
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(42 citation statements)
references
References 51 publications
(112 reference statements)
6
35
1
Order By: Relevance
“…According to our experiments, sinusoidal patterns are the most appropriate for inducing accommodation changes with our system, and we project a 1D sinusoid along the axis of the cylindrical power for those with astigmatism. These observations seem to be supported by findings in the opthalmology literature [Day et al 2009]. We used our system to project a sinusoidal pattern at various distances from the viewers, who were asked to focus at the pattern.…”
Section: User Evaluationsupporting
confidence: 82%
“…According to our experiments, sinusoidal patterns are the most appropriate for inducing accommodation changes with our system, and we project a 1D sinusoid along the axis of the cylindrical power for those with astigmatism. These observations seem to be supported by findings in the opthalmology literature [Day et al 2009]. We used our system to project a sinusoidal pattern at various distances from the viewers, who were asked to focus at the pattern.…”
Section: User Evaluationsupporting
confidence: 82%
“…On the other hand, chicks demonstrate both corneal and lenticular accommodation . Characteristics of accommodation that have been linked to emmetropisation and myopia include accommodative microfluctuations, accommodative lag, tonic accommodation, and blur interpretation…”
Section: Accommodationmentioning
confidence: 99%
“…This could be tested directly by measuring accommodative responses using an autorefractor. Stimuli that are less informative for the accommodative system might lead to greater uncertainty in the accommodative response; it would be predicted that this would lead to increased microfluctuations (Day et al, 2009). If an impoverished signal for accommodation is responsible for discomfort, this could be for at least two reasons.…”
Section: Discussionmentioning
confidence: 99%
“…MacKenzie et al (2010) have argued that the global amplitude of spatial frequency information is critical for driving accommodation responses: they consider only the Fourier amplitude spectrum in their model of how stimulus spatial frequency content affects accommodation responses. By contrast, Day, Gray, Seidel, and Strang (2009) make the case that the critical information for accommodation responses is contained in the steepness of the luminance gradients. It has been suggested that coarse accommodation responses might be driven by the low spatial frequencies, which are then refined by using the higher ones (Charman, 1979).…”
Section: Accommodation Responsesmentioning
confidence: 99%
See 1 more Smart Citation